Bioluminescent method using Photobacterium leiognathi strain AK-MIE for rapid screening of heavy metals - Kassim, Adibah (2020)
Anthropogenic activities have contributed to the release of harmful toxicants into the environment which will eventually end up in sediments and soils which are the foundation of food web. Application of instrumental analysis solely is time consuming, costly, and only limited to the concentration. Incorporating a rapid, sensitive, and cheap bioluminescent based bioassay could indicate the toxicity level and reduce analysis time and cost. However, commercially available system uses a test organism with an optimum temperature of 15ºC-25ºC that required an expensive thermostat. In this study, we aim to isolate bioluminescent bacteria with broad range of growth temperature to assess the toxicity of environmental samples. A new bioluminescent bacterium strain was isolated from squid (Loligo duvauceli) and identified as Photobacterium leiognathi strain AK-MIE (AKS01) using 16S rRNA phylogeny analysis. The bacterial culture was grown in a luminescent broth media with different concentrations (0%-0.6%) of peptone, yeast extract, and salt, and a wide range of pH (5.5-8) and temperatures (4ºC-50ºC). Analysis through OFAT showed the best concentrations were at 0.2% of peptone, 0.3% NaCl, and 0.4% yeast extract, at pH 7.5 and temperatures ranging from 22ºC to 33ºC. The optimisation of medium composition was carried out using Response Surface Methodology (RSM) and Artificial Neural Network (ANN) with four parameters employed (NaCl, peptone, yeast extract, and pH). The predicted optimum conditions by RSM (2.76% NaCl, 2.28% peptone, 0.34% yeast extract, and pH 6.83) and ANN (2.21% NaCl, 2.27% peptone, 0.39% yeast extract, and pH 6.94) produced 541,211.80 RLU and 541,986.20 RLU respectively. The coefficient of determination value (R2) for RSM (0.9440) and ANN (0.9934) indicate a high correlation between the experimental and predicted values with ANN showing a superior data fitting capability. The strain was tested with different concentrations of toxicants that showed inhibitive effects between the range of 0.001 to 100 mg/L for toxic metals and 0.01 to 1000 mg/L for both pesticides and xenobiotics. The toxicity effects were determined by measuring the luminescence after 15-30 minutes of incubation period. The results based on IC50 values at 30 minutes exposure time showed that the bacterium was most sensitive to mercury (0.00978 mg L-1) followed by cadmium (0.5288 mg L-1), copper (0.8117 mg L-1), silver (1.109 mg L-1), lead (10.71 mg L-1), chromium (36.17 mg L-1), zinc (72.83 mg L-1), and nickel (97.85 mg L-1). The high values of R2 (>0.95) indicate a good relationship between the toxicity of heavy metals and the bioluminescence inhibition. There was no marked bioluminescence inhibition for pesticides and xenobiotics. Twelve out of 20 sediment samples collected from different factories in Bangi and Seri Kembangan showed positive toxic responses with more than 30% luminescence inhibition. The highest luminescence inhibition recorded was from sample 2 (61.43%). The validation method carried out using Inductively Coupled Plasma-Mass Spectrometer (ICP-MS) proved the presence of mercury, copper, cadmium, lead, and silver. Ten sediment samples collected from the Tekala River as a control showed no toxic responses with minimal to none luminescence inhibition.